Identification of a Novel Alternaria alternata Strain Able to Hyperparasitize Puccinia striiformis f. sp. tritici, the Causal Agent of Wheat Stripe Rust - Zheng, Li; Zhao, Jie; Liang, Xiaofei; Zhan, Gangming; Jiang, Shuchang; Kang, Zhensheng (Frontiers in Microbiology, 2017)
The obligate bitrophic fungus Puccinia striiformis f. sp. tritici (Pst) causes stripe (yellow) rust on wheat worldwide. Here, we report a novel fungal strain able to hyperparasitize Pst. The strain was isolated from grey-colored rust pustules, and was identified as Alternaria alternata (Fr.: Fr.) keissler based on a combination of morphological characteristics and multi-locus (ITS, GAPDH, and RPB2) phylogeny. Upon artificial inoculation, the hyperparasite reduced the production and viability of urediniospores, and produced a typical grey-colored rust pustule symptom. Scanning electron microscopy demonstrated that the strain could efficiently penetrate and colonize Pst urediniospores. This study first demonstrates that A. alternata could parasitize Pst and indicates its potential application in the biological control of wheat stripe rust disease.